1997
DOI: 10.1007/bf02404767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and ionic strength on the adsorption of Cs, Sr, Eu, Zn, Cd and Hg byPseudomonas putida

Abstract: Abstract. Bacterial metal accumulation may influence the mobility and chemical form (speciation) of metals in the environment. The passive adsorption of six metals (Cs, St, Eu, Zn, Cd and Hg) by a soil bacterium, Pseudomonas puti&~, was studied in the present work. using a radiotracer batchdistribution technique. To replicate natural conditions, the adsorption was considered as a function of pH (4-10) and ionic strength (0.01 M and 0.1 M KCI) at a low metal concentration ( 10-s M). E putida exhibited a total m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 24 publications
2
18
0
3
Order By: Relevance
“…S5, the adsorption of Hg 2þ by E. coli Top10/pBATE2 bacteria decreased under high ionic strength condition, which agrees with that reported in a previous study (Ledin et al, 1997). The results indicated that the surface-displayed system seems not applicable to remediate mercury pollution in seawater.…”
Section: The Ph-regulated Regenerationsupporting
confidence: 82%
“…S5, the adsorption of Hg 2þ by E. coli Top10/pBATE2 bacteria decreased under high ionic strength condition, which agrees with that reported in a previous study (Ledin et al, 1997). The results indicated that the surface-displayed system seems not applicable to remediate mercury pollution in seawater.…”
Section: The Ph-regulated Regenerationsupporting
confidence: 82%
“…Specific to bacteria, this observation has been reported by several researchers (i.e. [27,[44][45][46]). In many systems, there are two competing factors that affect metal sorption.…”
Section: Dependence Of Metal Sorption On Phsupporting
confidence: 52%
“…Moreover, in a study conducted by Clausen [20], it was reported that Bacillus licheniformis CC01 could remove 93% of copper, 8% of Chromium and 45% of Arsenic while Pseudomonas putida could remove 25% of copper from nutrient agar. Ledin and co-workers [49] revealed in their report that Pseudomonas putida could remove Sr (80%), Eu (97%), Zn (70%), Cd (70%) and Hg (95%) in media containing 10 -8 M of the respective metals.…”
Section: Discussionmentioning
confidence: 99%